Validation of an oral assessment tool for classroom use - Muñoz T., Ana; Álvarez, Martha; Casals, Sergi; Gaviria, Sandra; Palacio, Marcela (Colombian Applied Linguistics Journal, 2003)
The purpose of this research study was to examine the rater reliability and the concurrent validity of the Language Center oral assessment rubric (LCR) with the KET (Key English Test) and PET (Preliminary English Test), Cambridge Examinations. Thirty two students from beginning and intermediate levels participated in the study. Validity estimations included both logical and empirical analyses. Results from logical analyses indicated that the rubric has construct validity. Empirical analyses were conducted by establishing patterns of correlations between the two sets of measures. Results showed low correlations between KET and LCR and from moderate to strong among LCR evaluators. Further, strong correlations between PET and LCR were found suggesting that both measure a similar construct. The results indicate the need to adjust the rubric to low level students and to develop teacher education programs where training toward consistency in evaluation will br conducted.